Phenotype reversion as “natural gene therapy” in Fanconi anemia by a gene conversion event - Persico, Ilaria; Fiscarelli, Ilaria; Pelle, Alessandra; Faleschini, Michela; Pasini, Barbara; Savoia, Anna; Bottega, Roberta (Frontiers in Genetics, 2023)
Somatic mosaicism appears as a recurrent phenomenon among patients suffering from Fanconi anemia (FA), but its direct prognostic significance mostly remains an open question. The clinical picture of FA mosaic subjects could indeed vary from just mild features to severe hematologic failure. Here, we illustrate the case of a proband whose FA familiarity, modest signs (absence of hematological anomalies, fertility issues) and chromosome fragility test transition to negative overtime were suggestive of somatic mosaicism. In line with this hypothesis, genetic testing on patient's peripheral blood and buccal swab reported the presence of the only FANCA paternal variant (FANCA:c.2638C>T, p.Arg880*) and of both parental alleles (the additional FANCA:c.3164G>A, p.Arg1055Gln), respectively. Moreover, the SNP analysis performed on the same biological specimens allowed us to attribute proband's mosaicism status to a possible gene conversion mechanism.Our case clearly depicts the positive association between somatic mosaicism and probands' favorable clinical course due the occurrence of the reversion event at the hematopoietic stem cell level. Since this condition concerns only a limited subgroup of FA individuals, the accurate evaluation of the origin and extent of clonality would be key to steer clinicians towards the most appropriate therapeutic decision for their FA mosaic patients.